Financial Distress Analysis of IDX Textile Companies 2019-2024: Zavgren and Altman - Rya, Merchy; Lambe, Kristian Hoegh Pride; Baharuddin, Baharuddin (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
As a developing country, Indonesia relies heavily on the industrial sector as a key driver of employment. Among various types of industries, labor-intensive industries dominate, particularly the textile industry, which serves as a major source of employment. This study aims to analyze the potential for financial distress in five textile sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2024. The analysis employs two bankruptcy prediction models: the Zavgren model and the Altman Z-Score model. Additionally, the Wilcoxon Signed-Rank Test is used to determine whether there is a significant difference between the results of the two models in predicting financial distress. The results show that, according to the Altman model, 21 samples (70%) are predicted to be in bankruptcy, 8 samples (26.67%) are in the critical zone, and only 1 sample (3.33%) is in a healthy zone. In contrast, the Zavgren model predicts 4 samples (13.33%) to be in bankruptcy, 4 samples (13.33%) in a critical condition, and 22 samples (73.33%) to be financially healthy. The Wilcoxon test results indicate a significant difference between the Zavgren and Altman models in predicting financial distress among the textile companies studied.